Experimental study on the integrated thermal management system based on composite phase change materials coupled with metal heating film. (25th February 2023) - Lv, Youfu; Luo, Weiming; Li, Chuanchang; Liu, Daifei; Chen, Jian; Zhuang, Yijie; Wu, Weixiong
Highlights: Constructed an integrated thermal management system with both heating and cooling functions. The continuous pulse heating method is proposed for low temperature heating. The effect of pulsed heating on battery thermoelectrical properties was studied. The integrated thermal management system displays an excellent temperature control performance." Abstract: Lithium-ion batteries (LIBs) have strict operating temperature requirements, and the higher or lower temperatures also accelerate LIBs performance degradation, even causing thermal runaway in extreme cases. In this study, an integrated battery thermal management system (IBTMs) based on metal heating films (MHF) with composite phase change materials (CPCMs) is constructed, enabling the thermal management system to combine both low-temperature heating and heat dissipation functions. In the low-temperature heating study, the continuous pulse heating method is innovatively proposed. When the resting to heating time ratio is 1:1, this method can increase the charge/discharge capacity of the battery module to 78.4 and 76.0 Ah, which is 99.3 % and 99.2 % of those under an ambient temperature of 10 °C, and the maximum temperature would not exceed 30 °C. In addition, when the battery module is charged and discharged with 1 C-rate under a high temperature of 40 °C, the maximum temperature and maximum temperature difference are controlled within 57.1 and 2.63 °C, respectively. Even if the maximum temperature of the battery module remains below the safe temperature of 60 °C during the continuous 6-cycle test process. The research in this study contributes to the development and practical application of the integrated thermal management system.